OPTN/SRTR 2020 Annual Data Report: VCA. (10th March 2022) - Hernandez, J. A.; Miller, J.; Oleck, N. C.; Porras‐Fimbres, D.; Wainright, J.; Laurie, K.; Booker, S. E.; Testa, G.; Israni, A. K.; Cendales, L. C.
Abstract: The first vascularized composite allograft (VCA) transplant in the United States was performed in 1998 in a 40‐year‐old man who received a laryngeal transplant after experiencing severe trauma to the throat 20 years before. The following VCA was a hand transplant in 1999 in a 37‐year‐old man who lost his left hand 13 years before. Since then, the field of VCA transplantation has made significant strides. On July 3, 2014, the Or gan Procurement and Transplantation Network (OPTN)/United Network for Organ Sharing (UNOS) oversight of VCA procurement and transplant in the United States went into effect. In the last decade, the number of candidates listed for and transplanted with VCA has increased. While patient demographic data, whether listed candidates or patients undergoing VCA transplant, is limited by sample size, the trend is a predominance toward a young/middle‐aged, White population. Overall outcomes data have been promising, with the vast majority of VCA transplants resulting in functioning grafts.